Polymer Brushes on Graphitic Carbon Nitride for Patterning and as a SERS Active Sensing Layer via Incorporated Nanoparticles; ACS Applied Materials and Interfaces; Vol. 12, iss. 8 - Sheng W. Wenbo; Li Wei; Tan Deming; Zhang Panpan; Zhang En; Sheremet E. S. Evgeniya Sergeevna; Schmidt B. V. K. J. Bernhard; Xinliang Feng; Rodriguez (Rodriges) Contreras R. D. Raul David; Jordan R. Rainer; Amin I. Ihsan (2020, 2020)
Title screen